The Efforts of the Deputy Principal of Madrasah for Student Affairs in Improving Discipline in Congregational Dzuhur Prayers at Mas Al-Maksum Stabat - Yendra, Muhammad Jodi; Hemawati, Hemawati; Pohan, Indra Satia (Lembaga Riset Mutiara Akbar, 2024)
Discipline is an action in obeying every rule in school. Discipline makes students more orderly and orderly in carrying out their lives and students also understand that discipline is very, very important for their future, because it can form students' personalities that are strong and useful for all groups. This research aims to determine the efforts of the deputy principal for student affairs in improving the discipline of midday prayer in congregation at MAS Al-maksum stabat. And to find out the supporting and inhibiting factors along with solutions to increase the discipline of midday prayers in congregation. the type of research used was qualitative research using observation, interview and technical data analysis techniques. In this study, the informants taken were the principal, deputy principal for student affairs, one homeroom teacher, two subject teachers, and one student. The findings of this research show that the efforts of the deputy principal for student affairs in improving discipline in midday prayers in congregation at MAS Al-maksum Stabat are quite good, then the supporting factor is that the deputy principals for student affairs work together to discipline students for midday prayers in congregation. The inhibiting factor is that there are still students who are less aware of congregational prayers due to a lack of understanding of religious knowledge. The solution to the inhibiting factors is that the principal, deputy principal for student affairs and also other teachers play an active role in this matter of worship, especially by setting an example and being at the forefront of its practice, and the deputy principal for student affairs being more assertive in giving appropriate sanctions/punishments. with existing rules so that students can improve their discipline.